RNA helicase DDX3 is a regulatory subunit of casein kinase 1 in Wnt-β-catenin signaling - Sirrenberg-Cruciat, Cristina-Maria; Dolde, Christine; Groot, Reinoud E. A. de; Ohkawara, Bisei; Reinhard, Carmen; Korswagen, Hendrik C.; Niehrs, Christof (Science, 2013)
Three Tales of Wnt Signaling - The Wnt signaling pathway has important roles in regulating many biological processes during development and is also implicated in the behavior of some cancer cells (see the Perspective by Berndt and Moon). Cruciat et al. (p. 1436, published online 14 February) describe the mechanism of action of a protein found in a screen for proteins that influence Wnt signaling. DDX3, a DEAD-box RNA helicase, is required for proper Wnt signaling in Xenopus and Caenorhabditis elegans. It appears to act not through its action as an RNA helicase or through adenosine triphosphate binding, but rather by interacting with the protein kinase, casein kinase 1, and promoting its activation. Huang et al. (p. 1441, published online 31 January) investigated the function of receptor-interacting protein kinase 4 (RIPK4), the product a gene whose mutation causes severe developmental defects in mice and humans. Over-expression of the protein in cultured human cells activated transcription of genes regulated by the Wnt signaling pathway, and loss of RIPK4 function inhibited Wnt signaling in Xenopus embryos. At the molecular level, RIPK4 interacted with the Wnt co-receptor LRP6 and the Wnt signaling adaptor protein DVL2 and promoted phosphorylation of DVL2. Habib et al. (p. 1445) used Wnt-immobilized beads to understand how external cues direct asymmetrical stem cell divisions. Spatially restricted Wnt signals oriented the plane of mitotic division and lead to pluripotency gene expression in the Wnt-proximal daughter cell while the more distal daughter cell acquired hallmarks of differentiation. Thus, asymmetric gene expression patterns can arise as a consequence of orientation by a short-range signal. - Casein kinase 1 (CK1) members play key roles in numerous biological processes. They are considered “rogue” kinases, because their enzymatic activity appears unregulated. Contrary to this notion, we have identified the DEAD-box RNA helicase DDX3 as a regulator of the Wnt-β-catenin network, where it acts as a regulatory subunit of CK1ε: In a Wnt-dependent manner, DDX3 binds CK1ε and directly stimulates its kinase activity, and promotes phosphorylation of the scaffold protein dishevelled. DDX3 is required for Wnt-β-catenin signaling in mammalian cells and during Xenopus and Caenorhabditis elegans development. The results also suggest that the kinase-stimulatory function extends to other DDX and CK1 members, opening fresh perspectives for one of the longest-studied protein kinase families. - A multifunctional protein is required for activation of casein kinase 1 in response to Wnt-β-catenin signaling. [Also see Perspective by Berndt and Moon] - A multifunctional protein is required for activation of casein kinase 1 in response to Wnt-β-catenin signaling. [Also see Perspective by Berndt and Moon]
Gesehen am 28.05.2021